Physiology and endocrinology symposium: Influence of cattle genotype (Bos indicus vs. Bos taurus) on oocyte and preimplantation embryo resistance to increased temperature - Lopes, Fabíola Freitas de Paula; Lima, Rafaela Sanchez de [UNESP]; Satrapa, Rafael Augusto [UNESP]; Barros, Ciro Moraes [UNESP] (Oxford University Press (OUP), 2013)
High environmental temperatures during the hot months of the year reduce reproductive performance in cattle. Summer heat stress depression in fertility is a multifactorial problem; however, there is evidence that the bovine germinal vesicle and maturing oocyte, as well as the early embryo, are major targets of the deleterious effects of heat stress. Such adverse effects are less pronounced in heat-tolerant breeds (Bos indicus) than heat-sensitive breeds (Bos taurus). This genetic variation results from the greater thermoregulatory ability and cellular thermoresistance of heat-tolerant breeds. Heat-induced oocyte cellular damage occurs in both cytoplasmic and nuclear compartments. Heat shock has been shown to reduce oocyte nuclear maturation, induce apoptosis, compromise oocyte cytoskeleton, and impair oocyte mitochondrial function and developmental competence. However, the oocyte cytoplasm is more susceptible to heat shock than the nucleus. This effect is greater for Bos taurus than Bos indicus oocytes. The detrimental effects of heat shock are also critical during the first cleavage divisions when most of the embryonic genome is inactive; however, the bovine embryo becomes more resistant to increased temperature as it proceeds through development. Several studies demonstrated that Bos indicus embryos are more thermotolerant than Bos taurus embryos. Adaptive changes involved in acquisition of thermotolerance are likely derived from changes in gene expression and (or) activity of biochemical molecules that control cellular functions against stress. Recently, molecules such as IGF-I and caspase inhibitor z-DEVD-fmk have been shown to exert a thermoprotective role, rescuing heat-induced oocyte and embryo cellular damage and developmental competence. Therefore, cattle genotype and thermoprotective molecules can be considered as an alternative to modulate the effects of increased temperature in reproductive function.
Keywords: Bovine; Embryo; Heat stress; Oocyte; Thermotolerance